Investors’ rational conformity to government’s excessive behavior in PPP project: Forms and measurement - Liu, Jiaqi; Liu, Haodong; Bu, Zehui; He, Peifen; Liu, Jicai (International Journal of Strategic Property Management, 2024)
In PPP projects, there is a tendency for investors to follow the government’s excessive behavior, which is not conducive to controlling the behavior risks of the project. Due to the differences in conformity purposes, it is important to determine the form and tendency of investor conformity to understand the reasons for conformity and propose control suggestions. Referring to the research of Song et al., the study constructs an initial scale that investor’s rational conformity to the government’s excessive behavior. 269 and 244 data are used for the pre-test and validation of the scale, respectively. After adjusting the scale and analyzing reliability and validity by using SPSS and AMOS, the forms of investor conformity are divided into abidance, compliance, and obedience. Meanwhile, the measurement scales of three conformity tendencies are determined. These findings are conducive to quantitatively evaluating the risk level of investors’ conformity and deepening managers’ understanding of rational investor conformity, which is beneficial for reducing the risk of investor conformity and thus reducing the risk of the government’s excessive behavior.